Morality as a cause, not only an effect, of evolution: Thomistic reflections on gene-culture coevolutionary theory - Lyons, Nathan (Heythrop journal, 2025)
Some recent philosophical analyses of gene-culture coevolutionary theory propose that morality is a contributing cause in (and not only an outcome of) human evolution. This paper considers implications of this idea for Thomistic moral theory. According to the coevolutionary account, the social practices of early human communities create selection pressures in favour of pro-moral adaptations, making the evolution of morality a ‘biocultural’ process in which culture in some respects drives biology. This position chimes with, and indeed advances, some core themes of Thomistic ethics, including: the abiding significance of moral passions; the centrality of practical reason; the social character of practical reason; moral realism; the naturalness of morality; the link between nature and normativity. Biocultural evolutionary theory can thus offer Thomistic ethicists some new ways to understand their old ideas. If it is true that morality is a cause and not only an effect of human evolution, then Thomists are invited to see morality as an even more natural phenomenon than they previously thought.